Evaluation of hemic system indicators in athletes in terms of adaptation to exercises - Oparina, O. N.; Anisimova, N. V.; Dogurevich, O. A. (Theory and Practice of Physical Culture, 2017)
The objective of the study was to assess the applicability of the hemic system indicators in athletes and non-athletes in terms of adaptation to physical loads. Conclusion: The informative value of the integrated survey of athletes increases significantly when assessing the blood values in dynamics - before and after muscular exercise at different stages of the annual training cycle, which makes it possible to determine the reserve capabilities of a number of blood system indicators.